Study of The Behavior of Abutment Piled Foundation due to Nearby Staged Embankment (Case Study: Kali Kandang Bridge on The North Ring Road of Lamongan) - Azkiya Nabila; Trihanyndio Rendy Satrya; Ria Asih Aryani Soemitro; Sifa Udukha (Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, 2025)
Kali Kandang Bridge is built on soft soil with low bearing capacity that uses a combination of Preloading, Prefabricated Vertical Drains (PVD), and Prefabricated Horizontal Drains (PHD) that require a long time to achieve a 90% consolidation degree. During the consolidation process, there is no other work that can be done. To increase time efficiency, shorten the PVD spacing or manage two or more works, such as piling bridge abutment, staged embankment, and consolidation process simultaneously can be done. But, embankment above soft soil near piled foundation can give additional forces to the pile so the study of behavior of abutment piled foundation due to nearby staged embankment and degree of consolidation should be done. This study analyzes the effects to piles if piling is carried out after consolidation is complete. Then, it analyzes the effects of variation of the PVD spacing of 0.75 m and 0.50 m, variations in embankment stages of 0.75 m/day, 1.00 m/day, and 1.25 m/day and variations in piling at various degrees of consolidation ranging from 10% to 90%. From the analysis, it was found that the variation of PVD installation spacing of 0.75 m and 0.5 m and the variation of embankment phasing of 0.75 m/day, 1.00 m/day, and 1.25 m/day did not provide a significant effect on either the soil settlement and consolidation time or the lateral deflection, pile settlement and forces in piles. On the other hand, pile driving at different consolidation degree variations showed a significant effect. The most critical condition where the foundation pile received the largest additional forces was on the foundation pile driven at a consolidation degree of 10%.